2018
DOI: 10.1186/s12986-018-0247-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Methionine and Homocysteine levels in Zucker diabetic fatty (ZDF) rats as a T2DM animal model after consumption of a Methionine-rich diet

Abstract: BackgroundAlthough alterations in the methionine metabolism cycle (MMC) have been associated with vascular complications of diabetes, there have not been consistent results about the levels of methionine and homocysteine in type 2 diabetes mellitus (T2DM). The aim of the current study was to predict changes in plasma methionine and homocysteine concentrations after simulated consumption of methionine-rich foods, following the development of a mathematical model for MMC in Zucker Diabetic Fatty (ZDF) rats, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
5
0
2
Order By: Relevance
“…Methionine is an essential sulfur-containing amino acid that contributes to both anabolic metabolism and the reduction of free radicals. One study recently observed that methionine levels were elevated in diabetic obese rats with leptin missense mutations[54], which is in line with the model of metabolic dysregulation proposed by Adams in an insulin resistant and obese state. In this model, he proposed that reduction in branched-chain α-keto acid dehydrogenase (BCKD) activity affected metabolism of α-ketobutyrate into propionyl-CoA.…”
Section: Amino Acidssupporting
confidence: 74%
“…Methionine is an essential sulfur-containing amino acid that contributes to both anabolic metabolism and the reduction of free radicals. One study recently observed that methionine levels were elevated in diabetic obese rats with leptin missense mutations[54], which is in line with the model of metabolic dysregulation proposed by Adams in an insulin resistant and obese state. In this model, he proposed that reduction in branched-chain α-keto acid dehydrogenase (BCKD) activity affected metabolism of α-ketobutyrate into propionyl-CoA.…”
Section: Amino Acidssupporting
confidence: 74%
“…Previous studies have shown that the mean protein and Met content in animal products is 16.5% and 3.17%, and their content in plant products is 9.8% and 1.27%, respectively (Ingenbleek, 2006). Increased Met intake is known to contribute to increased Hcy levels (Ramlau‐Hansen et al ., 2003; Kumar et al ., 2017; Han et al ., 2018). The consumption of meat‐ and dairy‐based products can also cause an increase in Hcy levels (Chambers et al ., 1999; Xiao et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Основной причиной значительного повышения уровня гомоцистеина в крови является генетически обусловленная дисфункция ферментов и кофакторов, связанных с процессом биосинтеза гомоцистеина [7,19,23]. Повышение гомоцистеина может быть связано также с нарушением диеты, связанной с излишним потреблением продуктов, богатых метионином (сыр, орехи, мясо, яйца, соя) [15], дефицитом фолатов, витамина В12 и, в меньшей степени, дефицитом витамина В6, что влияет на метаболизм метионина [11,27,32]. Гипергомоцистеинемия (ГГЦ) может сопровождать прием препаратов метионина, например, в бодибилдинге [24], где метионин является одной из самых важных аминокислот для набора мышечной массы [22,31].…”
Section: Introductionunclassified
“…), гипергомоцистеинемию воспроизводят различными способами, используя в зависимости от цели эксперимента адекватные методологические подходы, основанные на метаболизме метионина. Так, инъекции метионина либо гомоцистеина (фармакологический подход) [5,9,15], внутрижелудочное введение суспензии метионина [2,3] приводят к тяжелой форме ГГЦ. В экспериментах на мышах показано, что умеренная гипергомоцистеинемия может быть достиг-нута путем увеличения общего содержания метионина до 12-20 г/кг в пище [16] или воде [21].…”
Section: Introductionunclassified